Detection of pregnancy associated protein(s) in the sera of pregnant buffaloes - SINGH, S K; AGARWAL, S K; SHANKER, U (The Indian Journal of Animal Reproduction, 2023)
In the present study. attempt has been made to use enzyme linked immuno sorbent assay (ELISA) for the detection ofpregnancy-associated proteins in the scra of pregnant buffaloes. The blood samples from pregnant (n =25 . 30 days post inseminationtill term) and non-pregnant buffaloes (n=l 0) were collected by jugular vein puncture and indirect plate test and dot ELISA wasperformed with standard protocol using hyper immune sera raised against purified fractions of reproductive fluid from pregnantgenital tracts and placental extracts as a primary antibody solution . The optical density in indirect plate ELISA ranged from 0.515to 0.878 (Mean 0.717), 0.327 to 0.710 (Mt:an 0.562) for pregnant samples and from 0.251 to 0.469 (Mean 0338), 0.209 to 0.350(Mean 0.267) for non-pregnant sample using the anti- purified fraction of reproductive fluid and placental extract sera separately.Indirect plate ELISA revealed higher OD values for pregnant scra sam ples indicating presrnce of some proteins associated withpregnancy in the sera samples. In dot ELISA. out of 25 samples from pregnant buffaloes, positive color reaction was observed in 20(80%) and I 7(68%) sera samples using anti-purified fraction of reproductive tluid and placental extract sera separately, however, nocolor development was observed in 9(n= I 0. 90%) non pregnant samples . It appears that pregnancy associated proteins can bedetected in the sera of pregnant buffaloes further purification of these proteins mav enhance the accuracy.
Keywords: Pregnancy associated proteins; serum; buffalo; ELISA